Immunization Basics and Case-Based Discussion - Julia Belkowitz; Garnet Peter (Association of American Medical Colleges, 2014)
Abstract Introduction Vaccines are instrumental in preventing childhood death and disease. Despite their effectiveness pediatricians will often have to counsel parents and families on the importance of getting children vaccinated. Methods This 2.5 hour session begins with a PowerPoint presentation on the general concepts in immunization and a broad introduction of the spectrum of diseases potentially prevented by routinely recommended vaccines in the United States. The learners are then divided into and small groups for a facilitated discussion and an opportunity to apply the material presented in clinical scenarios. These materials are intended for use in clinical medicine or doctoring skills courses and are not intended to replace teaching about the infectious diseases in basic science coursework. Results This lecture and small-group discussion has been used with first-year medical students since 2007 as a part of the Physicianship Skills courses at our institution. The sessions have been well received according to student evaluations, and faculty facilitators (even non-pediatricians) have found the facilitator guide to be a helpful resource. Each year, there are approximately four exam questions from this session relating to mortality from vaccine preventable diseases and recommended vaccines for people of different ages. The mean percent of students selecting the correct answer for each of these knowledge questions ranges from 86% to 100%. Discussion At our institution, the PowerPoint presentation is given prior to the small-group discussion, but either item could be used separately as well. Finding a facilitator for each group is recommended as we found that students did not have a rich enough discussion when left to work through the cases independently.